Uji Sifat Organoleptik Patty Stick Patin Kelanggi Ditinjau Dari Ketebalan Dan Suhu Penggorengan - Sefhia Kurnia Gracelia; Any Sutiadiningsih; Asrul Bahar; Ita Fatkhur Romadhoni (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Patty stick is a processed product made from catfish, roasted young coconut and clover leaf puree which is processed using the deep frying technique. It is rectangular in shape with a length of 8 cm and a width of 2 cm which is used as a snack at any time. The aim of this research is 1) to determine the effect of thickness, temperature, and the interaction of thickness and temperature on the shape and color of fried patin kelanggi patty stick products. 2) to determine the nutritional content of the best patty stick products. This research method is experimental. The data collection technique used was observation through 5 trained panelists and 25 semi-trained panelists who were assisted with a line scale observation sheet (0-15 cm). The results showed that thickness had an effect on color and had no effect on the shape of fried patin kelanggi patty sticks. Temperature affects the color and has no effect on the shape of the fried patin kelanggi patty stick, and the interaction of thickness and temperature affects the color and has no effect on the shape of the fried patin kelanggi patty stick. The nutritional content of the best fried patin kelanggi patty sticks is 2 cm treated at a temperature of 160°C based on laboratory tests showing that per serving it has a carbohydrate content of 76.45%, protein 12.01%, fat 7.08%, fiber 2, 11%, water 2.31%.